Expanding Horizons – A Broad-Spectrum Review of Emerging Medical Applications of N-Acetylcysteine - Oskar Mikołajczyk; Aleksandra Suchołbiak; Aleksander Małachowski; Aleksandra Serafin; Katarzyna Naja; Karolina Baran; Jakub Zwardoń; Julia Sałata; Filip Bracichowicz (Quality in Sport)
N-acetyl-l-cysteine is a thiol-containing compound widely recognized for its antioxidant, mucolytic, and glutathione-replenishing properties. Historically established for use in acetaminophen toxicity and respiratory diseases, n-acetyl-l-cysteine has garnered growing interest for its broad therapeutic potential across diverse medical domains. This narrative review synthesizes evidence from meta-analyses published from January 2024 onwards, sourced from PubMed, to present emerging clinical applications of n-acetyl-l-cysteine. Findings suggest promising roles for n-acetyl-l-cysteine as an adjunctive therapy in managing rheumatoid arthritis, improving reproductive outcomes in women with polycystic ovary syndrome, and enhancing recovery following physical exertion by reducing oxidative stress and inflammation. While results for substance use disorders remain mixed, n-acetyl-l-cysteine’s modulation of glutamatergic and antioxidant pathways warrants further investigation. Nonetheless, n-acetyl-l-cysteine’s favorable safety profile and multifaceted biological actions underscore its potential in various clinical contexts. This review highlights medical areas of growing evidence on n-acetyl-l-cysteine’s efficacy while identifying gaps that necessitate further well-designed trials. Its aim is to inform about new research directions.